Expression pattern of three putative RNA-binding proteins during early development of the sea urchin Paracentrotus lividus - Röttinger, Eric; Besnardeau, Lydia; Lepage, Thierry (Gene Expression Patterns, 2006)
We report the expression patterns of three transcripts encoding RNA-binding proteins during early development of the Mediterranean sea urchin Paracentrotus lividus. Two of these genes encode KH-domains RNA-binding proteins closely related to the vertebrate neuro-oncological ventral antigen 1 (Nova) and RING Finger and KH-domain (RKHD). The third encodes the sea urchin ortholog of the polypyrimidine tract binding protein (PTB). Zygotic expression of nova and rkhd starts at mesenchyme blastula stage and is restricted to the presumptive endoderm territory. During gastrulation, expression of nova is restricted to the midgut and hindgut, while expression of rkhd become more complex and includes the foregut and hindgut territories as well as previously unknown territories within the ectoderm. PTB is first expressed ubiquitously but starting at the late gastrula stage, then PTB transcripts become highly enriched in the foregut and oral ectoderm. We further report that expression of nova and rkhd in the endomesoderm is under the control of the Wnt/beta-catenin pathway and occurs in a cell-autonomous manner while expression of rkhd and PTB in the oral ectoderm is regulated by Nodal signaling.